2015
DOI: 10.1007/s40265-015-0364-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Cilostazol: A Critical Review of the Literature

Abstract: Cilostazol is a unique antiplatelet agent that has been commercially available for over two decades. As a phosphodiesterase III inhibitor, it reversibly inhibits platelet aggregation yet also possesses vasodilatory and antiproliferative properties. It has been widely studied in a variety of disease states, including peripheral arterial disease, cerebrovascular disease, and coronary artery disease with percutaneous coronary intervention. Overall, cilostazol appears to be a promising agent in the management of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 85 publications
(146 reference statements)
2
40
0
2
Order By: Relevance
“…Trequinsin, another PDE3 inhibitor, also inhibits thrombin-induced activation of equine platelets (1820), however, to our knowledge, this is the first study testing cilostazol for platelet inhibitory effects in horses. Of the two tested PDE inhibitors, only cilostazol has been used as a thromboprophylactic drug in humans (34), with IBMX being largely an in vitro or ex vivo experimental tool. Since we and others have shown that the weaker non-selective PDE inhibitors, theophylline and pentoxifylline, are ineffective at inhibiting platelet activation when administered to horses (see text footnote 1) or tested ex vivo (20, 35), cilostazol has potential as a PDE inhibitor in horses.…”
Section: Discussionmentioning
confidence: 99%
“…Trequinsin, another PDE3 inhibitor, also inhibits thrombin-induced activation of equine platelets (1820), however, to our knowledge, this is the first study testing cilostazol for platelet inhibitory effects in horses. Of the two tested PDE inhibitors, only cilostazol has been used as a thromboprophylactic drug in humans (34), with IBMX being largely an in vitro or ex vivo experimental tool. Since we and others have shown that the weaker non-selective PDE inhibitors, theophylline and pentoxifylline, are ineffective at inhibiting platelet activation when administered to horses (see text footnote 1) or tested ex vivo (20, 35), cilostazol has potential as a PDE inhibitor in horses.…”
Section: Discussionmentioning
confidence: 99%
“…185 A selective inhibitor of phosphodiesterase type 3, it is believed to heighten the risk of fatal arrhythmias in patients with HF. It has never been directly studied in patients with HF; however, the increased risk is presumed to occur within 1 month of initiation because of the nature of the observed electrophysiological effects and extrapolation from the effects of oral milrinone, a pharmacologically similar medication.…”
Section: Cilostazolmentioning
confidence: 99%
“…The major side effect of cilostazol is bleeding, due to its antiplatelet activity, although its risk is low. 14) Our patient did not suffer from any side effects from cilostazol during the course.…”
Section: Discussionmentioning
confidence: 53%